Ramath: mathematics teaching app - Amadeo José Argüelles Cruz; Hiram David Cortés Díaz; Octavio Elias Piñal Ramírez (Centro de Estudios Financieros, 2023)
This paper presents the Ramath mobile application (app) and its second version using a head mounted display (HMD). Both use augmented reality with the support of game play mechanics in a non-game application, oriented to help 12 to 15 years old students (male and female) to learn several math subjects. We associate concepts such as «gamification» and «problem-based learning» (PBL) within the app, making the subjects much more interesting to the students and encouraging them to be fearless of math by taking advantage of the humans' psychological predisposition to engage in gaming. With the collected information from the research and the help of a predictive algorithm, we try to show how much the technology can help in education.